Expanding the Contributions of bell hooks: Through the Lens of Adult Education - Catherine H. Monaghan; Elice E. Rogers; Catherine A. (Adult Education Research Conference, 2008)
The purpose of this roundtable is to discuss hook’s influence in the field of adult education and her contributions. We will explore four key areas: 1) adult teaching and learning pedagogy, 2) adults and popular culture, 3) feminism and diverse women’s issues, and 4) diversity and liberatory pedagogy.
Keywords: adult education; feminist pedagogy; popular culture